Etiology of nosocomial infections and antibiotic resistance (level of antibiotic resistance) of identified pathogens in patients with traumatic chest injuries - Nikolai B. Esaulenko; Andrey A. Zaitsev; Rayana E. Sardalova; Sergey P. Kazakov (Consilium Medicum)
Background. Chest injuries and wounds are common during armed conflicts, with frequent nosocomial infections and mortality up to 35-45% [1-4]. Infectious complications associated with multidrug-resistant microorganisms are an urgent issue in the management of patients with trauma.